Different Benzendicarboxylate-Directed Structural Variations and Properties of Four New Porous Cd(II)-Pyridyl-Triazole Coordination Polymers - Zhao, Ying; Jing, Jin; Yan, Ning; Han, Min-Le; Yang, Guo-Ping; Ma, Lu-Fang (Frontiers in Chemistry, 2020)
Four new porous Cd(II)-based coordination polymers (CPs), namely [Cd(mdpt)2]•2H2O (1), [Cd2(mdpt)2(m-bdc)(H2O)2] (2), [Cd(Hmdpt)(p-bdc)]•2H2O (3) and [Cd3(mdpt)2(bpdc)2]•2.5NMP (4) have been synthesized successfully by the reactions of Cd(II) salts with a bitopic rigid 3-(3-methyl-2-pyridyl)-5-(4-pyridyl)-1,2,4-triazole (Hmdpt) and different benzendicarboxylate ligands, such as 1,3-benzenedicarboxylic acid (m-H2bdc), 1,4-benzenedicarboxylic acid (p-H2bdc) and biphenyl-4,4'-dicarboxylic acid (H2bpdc). Single-crystal X-ray diffraction analysis shows that complex 1 is a three-dimensional (3D) 2-fold interpenetrated 4-connected NbO framework based on mdpt- ligand; 2 reveals a 2D 3-connected hcb network. Interestingly, complex 3 presents a 3D rare interpenetrated double-insertion supramolecular net via 2D •••ABAB••• layers and can be viewed as a (4,6)-connected fsh net with the point symbol of (43.63)2(46.66.83); while complex 4 displays a 3D 8-connected sqc117 framework with the point symbol of (36.412.58.62). Gas sorption behaviors of 1 and 4 for N2, CH4 and CO2 have been studied in detail at different temperatures, indicating that complex 4 has the preferable sorption than 1 and can be the potential storage and separation material for CO2. In addition, the thermal and luminescent properties of 1–4 have also been studied in the solid state.